Low-Complexity Blind Carrier Phase Recovery for C-mQAM Coherent Systems - Ping Zhang; Hongliang Ren; Mingyi Gao; Jin Lu; Zichun Le; Yali Qin; Weisheng Hu (IEEE Photonics Journal, 2019)
A novel carrier phase recovery algorithm is proposed for coherent optical systems with circular multilevel quadrature amplitude modulation (C-mQAM). After amplitude segmentation and phase rotation, the particular distribution of the constellation points in a C-mQAM signal is exploited to construct a special cost function to provide a rough estimate of phase noise. The cost function can be replaced with a simple cosine function, and only two or three test phases are required for the calculation of its parameters. The performances of different cost functions are compared and simulation results show that the cost function can be chosen with the high phase noise tolerance and low computational complexity. Maximum-likelihood phase noise estimation algorithm is combined with the proposed algorithm to mitigate residual phase noise. Compared to the single-stage blind phase search and n-phase-shift keying partitioning algorithms, the numerical results demonstrate that the proposed two-stage algorithm shares similar phase noise tolerance and offers a lower computational complexity for a 28-GBaud back-to-back coherent optical QAM transmission system.